Digital Activism dalam Membangun Kesadaran Anak Muda Terhadap Isu Rokok (Studi pada Instagram Indonesian Youth Council for Tactical Changes) - Assyifa Uzzahro Khoerunnisa; Leonard Dharmawan (Science and Education Journal (SICEDU), 2026)
The high prevalence of young smokers in Indonesia is influenced by the tobacco industry’ssystematic strategy of targeting youth as “replacement smokers” through digital spaces. Thiscondition has created a narrative contest between the tobacco industry and tobacco controlmovements, highlighting the importance of digital activism. This study aims to analyze themechanism of connective action in the digital activism carried out by the Instagram account of theIndonesian Youth Council for Tactical Changes (IYCTC) in raising youth awareness of smokingissues. This research employed a descriptive qualitative approach with a case study method. Datawere collected through in-depth interviews, thematic analysis of IYCTC’s Instagram content,documentation, and literature review. Data analysis was conducted using the Miles and Hubermanmodel through data reduction, data display, and conclusion drawing. The findings reveal thatIYCTC’s connective action is built through message personalization, the use of digital technology,and the strengthening of communication networks. These strategies are implemented through youthrelated issue framing, informal language, interactive visuals, and call-to-action content thatencourages organic audience participation through Instagram features.